Can enterprise digitalization promote green technological innovation? evidence from China’s manufacturing sector - Zang, Jinxiang; Teruki, Neilson; Ong, Sharon Yong Yee; Wang, Yan (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
China’s manufacturing industry is characterized by high energy consumption and high pollution, which urgently requires resolution through green technological innovation. This study focuses on China’s A-share listed manufacturing enterprises to explore their development path for green technological innovation. The study primarily employs statistical regression analysis to uncover the causal link between digitalization and green technology innovation. The study’s conclusion indicates that the digitalization of manufacturing enterprises has significantly promoted green technological innovation. This conclusion remains robust after a series of tests, including alternative variable measurements, instrumental variable (IV) estimation, and counterfactual analysis. Mechanism analysis reveals that digitalization can enhance green technological innovation by improving human capital and innovating business models. The results of the heterogeneity analysis show that the effect of digitalization on promoting green technological innovation is more pronounced in enterprises with higher green awareness among senior executives, high green credit, non-heavy pollution industries, a higher level of existing green technological innovation, and larger enterprise scale. The government should increase support for the digital transformation of enterprises and promote green technological innovation by enhancing the green awareness of enterprise senior executives, optimizing green credit policies, formulating transformation policies for heavily polluting enterprises, implementing differentiated policies based on enterprise scale, and promoting digital transformation.